Conditioned Pain Modulation: Comparison of the Effects on Nociceptive and Non-nociceptive Blink Reflex. (1st August 2021) - Kinukawa, Tomoaki Alex; Inui, Koji; Taniguchi, Tomoya; Takeuchi, Nobuyuki; Sugiyama, Shunsuke; Nishihara, Makoto; Nishiwaki, Kimitoshi; Kakigi, Ryusuke
Highlights: CPM was observed objectively using blink reflexes and a cold stimulus to the hand. Nociceptive- but not non-nociceptive blink reflex was suppressed. Perceived sensations were suppressed for both noxious and innocuous stimuli. Effects on the sensation suggested mechanisms higher than the medulla. Results of blink reflex indicated pain-specific mechanisms at medullary dorsal horn. Abstract: Although conditioned pain modulation (CPM) is considered to represent descending pain inhibitory mechanisms triggered by noxious stimuli applied to a remote area, there have been no previous studies comparing CPM between pain and tactile systems. In this study, we compared CPM between the two systems objectively using blink reflexes. Intra-epidermal electrical stimulation (IES) and transcutaneous electrical stimulation (TS) were applied to the right skin area over the supraorbital foramen to evoke a nociceptive or a non-nociceptive blink reflex, respectively, in 15 healthy males. In the test session, IES or TS were applied six times and subjects reported the intensity of each stimulus on a numerical rating scale (NRS). Blink reflexes were measured using electromyography (R2). The first and second sessions were control sessions, while in the third session, the left hand was immersed in cold water at 10 °C as a conditioning stimulus. The magnitude of the R2 blink and NRS scores were compared among the sessions by 2-way ANOVA. Both the NRS score and nociceptive R2 were significantly decreased in the third session for IES, with a significant correlation between the two variables; whereas, TS-induced non-nociceptive R2 did not change among the sessions. Although the conditioning stimulus decreased the NRS score for TS, the CPM effect was significantly smaller than that for IES ( p = 0.002). The present findings suggest the presence of a pain-specific CPM effect to a heterotopic noxious stimulus.